2021
DOI: 10.1248/bpb.b20-00737
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> and <i>in Vivo</i> Comparative Study of Oral Nanoparticles and Gut Iontophoresis as Oral Delivery Systems for Insulin

Abstract: Multiple daily injections of insulin for diabetes cause many hazards for diabetic patients. Oral noninvasive insulin delivery could be more convenient and less painful than parenteral route. In past decades transdermal iontophoresis had been studied for insulin delivery across the skin with or without chemical permeation enhancers. However, the results of these studies were not efficacious and serum insulin levels were not therapeutically effective. In the present study an advanced technology "gut iontophoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To diminish the unwanted complications of insulin administration and increase the patient’s compliance, various research teams tried to incorporate it in multiple carriers for oral administration [ 146 , 147 , 148 ]: liposomes [ 149 , 150 ] mixed micelles [ 151 , 152 ], nanoparticles [ 153 , 154 , 155 ], intestinal patches [ 156 ]. Current studies also explore other access ways for insulin administration: intranasal [ 157 , 158 , 159 ], transdermal [ 160 , 161 ], and sublingual [ 162 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…To diminish the unwanted complications of insulin administration and increase the patient’s compliance, various research teams tried to incorporate it in multiple carriers for oral administration [ 146 , 147 , 148 ]: liposomes [ 149 , 150 ] mixed micelles [ 151 , 152 ], nanoparticles [ 153 , 154 , 155 ], intestinal patches [ 156 ]. Current studies also explore other access ways for insulin administration: intranasal [ 157 , 158 , 159 ], transdermal [ 160 , 161 ], and sublingual [ 162 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…PermeGear's Franz diffusion cells (Hellertown, PA, USA) were effectively employed to extensively investigate the rat's intestinal segment. These cells possess a remarkable volume of 20 mL and a vast diffusion area of 2.91 cm 2 [66].…”
Section: Ex Vivo Release Studymentioning
confidence: 99%
“…An in vitro permeation study indicated that iontophoresis aided in the permeation of insulin across the intestinal membrane as compared to passive diffusion. An in vivo permeation study further justified the effectiveness of iontophoresis in consistently delivering insulin across the intestinal membrane [ 133 ]. Similarly, the use of iontophoresis across intestinal cells resulted in improved paracellular transport of insulin due to the opening of the tight junctions.…”
Section: Advancements In Insulin Delivery Technologymentioning
confidence: 99%